Reflooding with internal boiling of a heating model porous medium with mm-scale pores. (August 2016) - Sapin, P.; Gourbil, A.; Duru, P.; Fichot, F.; Prat, M.; Quintard, M.
Highlights: A quasi-2D porous medium made of a bank of mm-scale cylinders was built. Each cylinder is a Pt-100 probe used both as a heating element and a thermometer. Reflooding experiments of this dry, superheated model porous medium were conducted. During reflooding, 3 different macroscopic zones are identified and characterized. Parametric studies show the influence of injection flow rate and heating power. Abstract: This paper presents a pore-scale experimental study of the reflooding of a two-dimensional model porous medium. The objective is to better understand the reflooding mechanisms in play in the context of nuclear reactor safety. The hot debris bed that forms in a nuclear reactor following a loss of coolant accident is comparable to a heat-generating porous medium. Its cooling by water reflooding involves intense boiling mechanisms that must be modeled properly to assess mitigation procedures. The experimental study presented in this paper focuses on the phenomenology of reflooding of a model porous medium composed of a bank of mm-scale heating cylinders placed between two ceramic plates. A Fluorinert™ liquid, HFE-7000, is injected at a temperature close to saturation into the dry and superheated porous medium. Each cylinder of the test section is used both as a heating element and a temperature probe, which enables to track the evolution of the three different macroscopic zones identified during cooling of the system. The reflooding dynamics, in particular the cooling fronts velocities, are thus determined thanks to pore-scale thermal measurements together with direct visualizations. The influence of the injection flow rate and of the heating power are studied in a parametric way.